Mathematical Modelling of the Growth Curve of Vibrio sp. Isolate MZ Grown in Seawater Medium (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
Pollution in the environment is deteriorating the ecology due to human activities in a large array of industrial and agricultural sectors. Bioassay of polluted waters using bioluminescent bacterium has been touted as one of the most economical, rapid and sensitive tests. The growth of the bacterium on seawater medium exhibited a typical sigmoidal profile. To extract important growth parameters useful for further modelling exercise, various primary growth models were utilized in this study such as Modified Logistic, modified Gompertz, modified Richards, modified Schnute, Baranyi-Roberts, von Bertalanffy, Huang and the Buchanan three-phase model. The best performance was Huang model with the lowest value for RMSE, AICc and the highest value for adjusted R2. The AF and BF values were also excellent for the model with their values were the closest to 1.0. The Huang parameters, which include A or Y0 (bacterial growth lower asymptote), ïm (maximum specific bacterial growth rate), ï¬ (lag time) and Ymax (bacterial growth upper asymptote) were 7.866 (95% confidence interval of 7.850 to 7.883), 0.329 (95% confidence interval of 0.299 to 0.359), 1.543 (95% confidence interval of 1.303 to 1.784) and 8.511 (95% confidence interval of 0.299 to 0.359).
Keywords: mathematical modelling, Vibrio sp., Hydrocarbon, bacterial growth, Huang